2020
DOI: 10.1126/sciadv.aba5672
|View full text |Cite
|
Sign up to set email alerts
|

Increased PIP3 activity blocks nanoparticle mRNA delivery

Abstract: The biological pathways that affect drug delivery in vivo remain poorly understood. We hypothesized that altering cell metabolism with phosphatidylinositol (3,4,5)-triphosphate (PIP3), a bioactive lipid upstream of the metabolic pathway PI3K (phosphatidylinositol 3-kinase)/AKT/ mTOR (mammalian target of rapamycin) would transiently increase protein translated by nanoparticle-delivered messenger RNA (mRNA) since these pathways increase growth and proliferation. Instead, we found that PIP3 blocked delivery of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Messenger RNA (mRNA) delivery holds great promise for the prevention and treatment of various diseases by either replacing or supplementing missing or inadequately expressed endogenous proteins . Its advantages, including no genomic integration, faster protein expression, and no need for nuclear uptake, have enabled the design of safe and highly efficient delivery systems based on mRNA to develop a wide range of therapeutic applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Messenger RNA (mRNA) delivery holds great promise for the prevention and treatment of various diseases by either replacing or supplementing missing or inadequately expressed endogenous proteins . Its advantages, including no genomic integration, faster protein expression, and no need for nuclear uptake, have enabled the design of safe and highly efficient delivery systems based on mRNA to develop a wide range of therapeutic applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A second way to improve the nanoparticle discovery pipeline is to understand which small animals best predict delivery in a non-human primate. Species variability can derive from physiological differences in basal metabolic rates 212 , which can affect nanoparticle delivery 213 215 , or differences in serum lipids 216 , which can affect the colloidal stability, biodistribution, cellular interactions, toxicity and clearance of the resulting nanoparticle coronas 217 . Additional species variability probably derives from the mass of a given tissue, relative to the total animal weight, which is not conserved (Fig.…”
Section: The Pathway To Clinical Rna Deliverymentioning
confidence: 99%
“…Specifically, several lines of evidence now suggest that pathways governing endogenous mRNA translation or metabolism may influence the efficiency with which LNP‐mediated mRNA delivery leads to functional protein. [ 21–26 ] In one example, researchers knocked down genes related to the mammalian target of rapamycin (mTOR) pathway in order to investigate their impact on LNP functional delivery. [ 21 ] They found that knocking down Rab4a and Rab5a, proteins necessary for early endosomal trafficking and endosomal recycling, had no impact on LNP delivery, whereas knocking down Rab7a, a protein necessary for endosomal maturation and late endosomal trafficking, significantly reduced LNP delivery.…”
Section: Delivering Rna To Diseased Cells Is An Inefficient Multistep Processmentioning
confidence: 99%
“…Additional data support the hypothesis that mTOR signaling, or signaling pathways that interact with the mTOR pathway, may influence delivery. [ 22 ] Recently, scientists found that the bioactive lipid phosphatidylinositol (3,4,5)‐triphosphate (PIP3) reduces LNP‐mediated mRNA delivery by changing a cell's metabolic state. [ 22 ] Based on transcriptomic and metabolomic analyses, researchers concluded that reductions in LNP delivery could be mediated by two potential mechanisms: first, that PIP3 induces consumption of cellular resources, limiting resources available for the translation of exogenously delivered mRNA; second, that PIP3 induces a catabolic cell response that triggers protein degradation and decreased translation.…”
Section: Delivering Rna To Diseased Cells Is An Inefficient Multistep Processmentioning
confidence: 99%
See 1 more Smart Citation